Distribution of Chlamydia trachomatis ompA genotypes and its association with abnormal cervical cytology among women of reproductive age in Shenzhen, China - Liu, Lan-lan; Sun, Si; Zhang, Li; Wu, Qiu-hong; Tian, Li-shan; Li, Bo; Chen, Xiang-sheng; Luo, Zhen-zhou (Frontiers in Public Health, 2022)
Background Many studies have focused on the distribution and specific clinical symptoms caused by Chlamydia trachomatis. Still, relatively few studies have focused on the associations between Chlamydia trachomatis genotypes and cervical intraepithelial lesions. Objectives This study was conducted to determine the distribution of Chlamydia trachomatis genotypes and its associations with cervical intraepithelial lesions among women of reproductive age. The presence of other STIs coinfection was also evaluated. Study Design 9090 women who met eligibility criteria were collected cervical swabs after providing informed consent, and 375 were Chlamydia trachomatis positive. In this study, 375 Chlamydia trachomatis positive cervical swabs from the population were collected. Chlamydia trachomatis DNA was extracted and amplified by nested-PCR, and then amplicons were sequenced and genotyped based on ompA gene. Human papillomavirus (HPV) DNAs tests were completed by the center of BGI Health clinical laboratory, Shenzhen, China. A Thin-Prep cytology test (TCT) was used to determine cervical intraepithelial lesions. Vaginal cleanliness was evaluated by smear microscopy. Chi-square tests and multivariate logistic regression analyses were performed to evaluate the associations between Chlamydia trachomatis, HPV and cervical intraepithelial lesions. Results 9090 cervical swabs were tested, and 375(4.1%) were Chlamydia trachomatis positive. The prevalence of coinfection with Neisseria gonorrhoeae, Candida albicans, Trichomonas vaginitis, Vulvovaginal candidiasis, and HPV were 0.8%, 2.7%, 2.4%, 10.1% and 15.5%, respectively. Among 375 Chlamydia trachomatis positive cervical swabs, 306 were genotyped successfully, and nine genotypes were identified. The most common genovar was E (25.16%,77/306), followed by J (22.55%, 69/306), F (17%, 52/306), D (14.4%, 44/306), K (7.2%, 22/306), G (6.9%, 21/306), H (5.2%, 16/306), B (1.0%, 3/306), Ia (0.7%, 2/306). Genotype H was associated with abnormal cervical cytology (p=0.006, aOR=8.16 (1.86-36.6)). However, this study observed no association between other Chlamydia trachomatis genotypes and vaginal discharge, either adverse pregnancy outcomes or reproductive tract symptoms. Conclusions Chlamydia trachomatis genotype H may be a high risk factor for cervical intraepithelial lesions, which is useful for treatment and management measures for patients with cervical intraepithelial lesions.